2022
DOI: 10.4314/jagst.v21i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver factors influencing nutritional status of preschool children in Mwingi West, Kitui County Kenya

Abstract: Children are at an increased risk of malnutrition, with many undernourished children being highly susceptible to preventable premature death and morbidity. Insufficient dietary intake, infections, food insecurity, and inadequate care are the main causes of child malnutrition. These factors are sequentially influenced by caregivers’ characteristics. Despite this, the effect of a caregiver’s characteristics on a child's nutrition status has not been exhaustively studied in rural areas of Kenya. It is important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…The results also showed that female respondents were the majority (57%) of the males, comprising the remaining 43%. This is similar to other COVID-19-related studies where women's participation was higher than men's (Kudaisi, 2021); [8]. The majority (49%) had completed their secondary school level of education.…”
Section: Characteristics Of Respondentssupporting
confidence: 89%
“…The results also showed that female respondents were the majority (57%) of the males, comprising the remaining 43%. This is similar to other COVID-19-related studies where women's participation was higher than men's (Kudaisi, 2021); [8]. The majority (49%) had completed their secondary school level of education.…”
Section: Characteristics Of Respondentssupporting
confidence: 89%